2019
DOI: 10.1021/acs.jpcc.9b02935
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Iridium Oxide Cluster Anions IrnOm (n = 5–8) with Sequential Oxidation: Binding Mode of O Atoms and Ir Framework

Abstract: Geometric structures of small cluster anions of iridium oxide Ir n O m – (n = 5–8, m = 0–14) were investigated by ion mobility mass spectrometry (IMMS) and theoretical calculation to clarify the evolutional behavior of the binding modes of the O atoms and the motif of the Ir frameworks as a function of m. The collision cross sections (CCSs) for n = 5–7 determined by IMMS showed a monotonic increase with m, whereas those for n = 8 dropped abruptly by ∼10% at m = 11, which otherwise gradually increased with m. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…For dissociative adsorption of NO, one common trend is that the O atom prefers to adsorb as terminal-O (μ 1 ). This was also found for dissociative adsorption of O 2 onto anionic Ir clusters, as revealed by ion mobility measurements . In addition, Zhou and coworkers reported that up to three O atoms adsorb on-top on pyramidal Ir 5 + .…”
Section: Discussionsupporting
confidence: 55%
“…For dissociative adsorption of NO, one common trend is that the O atom prefers to adsorb as terminal-O (μ 1 ). This was also found for dissociative adsorption of O 2 onto anionic Ir clusters, as revealed by ion mobility measurements . In addition, Zhou and coworkers reported that up to three O atoms adsorb on-top on pyramidal Ir 5 + .…”
Section: Discussionsupporting
confidence: 55%
“…A similar feature was repeatedly observed in our previous study of the structure assignment of transition metal oxide cluster ions. 31,34–45 For example, similar metal–oxygen–metal bonding structures were observed for the metal oxide cluster ions of group 4 (Ti 35 ), group 5 (V 37 and Nb 31 ), group 6 (Cr 39 ), group 8 (Fe 40 ), group 9 (Co 41 ), group 10 (Ni 42 ), group 11 (Cu 43 ), and group 12 (Zn 44 ).…”
Section: Resultsmentioning
confidence: 60%
“…Ion mobility mass spectrometry (IMMS) on small Ir-O clusters indicated that the bridging m2-O motif is favored by increasing the cluster size and the number of O atoms bound on Ir atoms. 53 On this ground, we tentatively assign the excessive cathodic charge appearing after the OER to the protonation of the surface bridging O species, oxidized during the preceding OER, occurring simultaneously with the injection of a higher number of species with low mass, e.g. H + /H 2 O, than in the subsequent sweeps.…”
Section: (B) Below)mentioning
confidence: 85%